(untitled) (Palíndromo, 2025)
The “René Brusau” Provincial Museum of Fine Arts is unique in its kind; in addition to promoting, exhibiting, and researching the arts of the Chaco region, it has the mission of preserving the works that are part of the province’s heritage. The legislation of the current province of Chaco (Argentina) recognizes the languages and cultural diversity of the population that existed prior to the colonization campaigns carried out since the late 19th century in the National Territory. However, until recently, pieces produced by Indigenous communities were not included in exhibitions of Chaco’s artistic heritage, nor did they appear in the contemporary art sections of museums or cultural institutions. The discussion about their artistic status has gained relevance in recent years, alongside a series of actions and interventions carried out by heritage management sectors and researchers focused on Chaco’s arts—through academic studies, museum curatorial projects, and artistic interventions. This article aims to reflect on some of the actions and interventions that have taken place within the museum space by artists and cultural field agents, through an analysis of the institution’s fundamental frameworks: its collection and exhibitions. It addresses ideological, exhibition design, and curatorial variables, taking into account intellectual debates and the development of institutional policies that have been proposed in relation to these matters.